How many English Words do the Senior High School Students Acquire per Week? - Ari Nurweni (TEFLIN, 1997)
Abstract: The 1984 SMA English curriculum states that SMA graduates are expected to master 4000 words. The curriculum also specifies the topics and then umber of words to be exposed to SMA students for each week (30 words per week). If it is accepted that each semester consists of 15 weeks, and each week the students actually learn 30 different words, then SMA graduates only learn about 2700 different words during their study at senior high school. Therefore, in my opinion the number of 4000 words also includes the words that should have been learnt by the them at SMP, that is, 1500 words according to the updated 1975 SMP English curriculum. However, Nababan (1984) states that we tend to forget about 40% of the words we have learned. If this is accepted, theoretically SMA graduates will only acquire about 2520 of the 4200 words (if the students only learn 2700 and 1500 at SMA and SMP respectively). The figure suggests that on average the students acquire about 14 different words per week during their study at SMP and SMA (2520 words divided by 12 semesters x 15 weeks).